Polydispersed flow modelling using population balances in an adaptive mesh finite element framework. (6th April 2016) - Bhutani, Gaurav; Brito-Parada, Pablo R.; Cilliers, Jan J.
Abstract : Highlights: An open-source finite element framework for modelling polydispersed flows is presented. Eulerian–Eulerian flow equations coupled to population balance equation (DQMOM). Model verification and benchmarking presented. Fully-unstructured, non-homogeneous, anisotropic mesh adaptivity applied. This is the first time mesh adaptivity is applied to external coordinates of the PBE. Abstract: An open-source finite element framework to model multiphase polydispersed flows is presented in this work. The Eulerian–Eulerian method was coupled to a population balance equation and solved using a highly-parallelised finite element code—Fluidity. The population balance equation was solved using DQMOM. A hybrid finite element–control volume method for solving the coupled system of equations was established. To enhance the efficiency of this solver, fully-unstructured non-homogeneous anisotropic mesh adaptivity was applied to systematically adapt the mesh based on the underlying physics of the problem. This is the first time mesh adaptivity has been applied to the external coordinates of the population balance equation for modelling polydispersed flows. Rigorous model verification and benchmarking were also performed to demonstrate the accuracy of this implementation. This finite element framework provides an efficient alternative to model polydispersed flow problems over the other available finite volume CFD packages.